Evaluating the Contributions of Dynamic Flow to Freezing of Gait in Parkinson's Disease - Chad A. Lebold; Q. J. Almeida (Parkinson's Disease)
Although visual cues can improve gait in Parkinson's disease (PD), their underlying mechanism is poorly understood. Previous research suggests that cues contribute optical flow that is essential to elicit gait improvement. The present study manipulated how optic flow was provided, and how this might influence freezing of gait (FOG) in PD. Therefore, three groups; 15 PD FOG, 16 PD non-FOG, and 16 healthy controls were tested in 3 narrow doorway conditions; baseline (Narrow), ground lines (Ground), and laser (Laser). Step length indicated that the PD FOG group was only able to improve with ground lines, while the laser increased gait variability and double support time. These results suggest that optic flow in itself is not enough to elicit gait improvement in PD. When PD patients use visual cues, gait becomes less automatically controlled and hence preplanned conscious control may be an important factor contributing to gait improvement.